Pathways of tourism synergistic development driving construction of beautiful and harmonious countryside from a configurational perspective - TAN Jiaxin, WANG Kai, GAN Chang (Ziyuan Kexue)
[Objective] This study aims to clarify the pathways through which tourism synergistic development drives the construction of beautiful and harmonious countryside from a configurational perspective, thereby providing references for comprehensively advancing the rural revitalization strategy. [Methods] Using panel data from 30 provinces (autonomous regions, municipalities) in China from 2010 to 2021, the sequential polygon area method was employed to evaluate the development level of beautiful and harmonious countryside. The dynamic qualitative comparative analysis (QCA) method was utilized to explore the configurational pathways of tourism synergistic development in driving the construction of such countryside. [Results] (1) Three configurational pathways were formed with service entities, economic environment, social security, and development status as core conditions and business vitality, ecological environment, policy environment, innovation capacity, and market potential as peripheral conditions. They could promote the construction of beautiful and harmonious countryside, with substitution effects observed between ecological environment and innovation capacity. (2) The pathways of tourism synergistic development in driving the construction of beautiful and harmonious countryside exhibited spatial heterogeneity. The three configurational pathways demonstrated a relatively high degree of consistency in the eastern developed regions and western resource-rich regions, while those in the central regions exhibited a moderate level of consistency. In contrast, the northeastern and north regions showed relatively limited effectiveness of tourism synergistic development in promoting the construction of beautiful and harmonious countryside. [Conclusion] Synergistic development of tourism contributes to promoting the construction of beautiful and harmonious countryside. It is recommended that the rural tourism industrial elements should be integrated through synergistic mechanisms, the modular development of the value chain be optimized, and the differentiated measures be implemented to further enhance the new driving forces for rural revitalization.